Product Innovation and Its Impact on Firm Competitiveness: Evidence from PT Martabak Mak Yung - Amar Al Kadri; Wulan Sari Kifki Telaumbanua; Farihah Nabila f (Yayasan Bayt Shufiya Nusantara, 2025)
The martabak egg business represents a traditional culinary sector with significant potential in Indonesia's economy. Despite its popularity, martabak producers face increasing challenges in maintaining business sustainability and remaining competitive in a rapidly evolving market. This study examines the role of product innovation in enhancing the competitiveness of PT Martabak Mak Yung to ensure its growth and long-term sustainability. Using a descriptive qualitative approach supported by in-depth interviews, the findings indicate that product innovation is a key driver of business success. Strategies such as diversifying fillings, offering variations in spiciness levels, providing different portion sizes, and improving packaging have proven effective in attracting and retaining customers. In addition, competitive advantages including homemade thin crispy skin, premium filling options, and the signature cuko sambal contribute to distinguishing the brand in both traditional and digital markets. These innovations not only enhance customer satisfaction but also boost business performance, as evidenced by a 12–18% increase in online customer engagement. The study highlights that continuous product innovation is essential for PT Martabak Mak Yung to sustain its market position and adapt to changing consumer preferences in the modern culinary landscape.